Kehidupan Sesudah Kematian dalam Paham Dayak Baya Busang dan Gereja Katolik: Tinjauan Eskatologis - Wilfridus Samdigawijaya; Agustinus Aristoteles Lawing (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2022)
This study describes the understanding of life after death according to the Dayak Bahau tribe and the Catholic Church. The approach used is a descriptive qualitative approach with interview methods and secondary data collection. The results of the study show that the Dayak Bahau and the Catholic Church both believe in eternal life. In eternal life, people who die can experience a happy eternal life as well as an unhappy eternal life. The Dayak Bahau tribe and the Catholic Church believe that the life circumstances experienced by those who die in eternal life are absolutely the authority of the Almighty. The Traditional Ceremony of Death in the Culture of the Dayak Bahau tribe which is carried out has in common with the recommendation to pray for people who die in the Catholic Church, namely that the deceased experience the convenience of achieving a happy eternal life.